Tudo que é olimpico desmancha no ar: os Jogos Pan-Americanos Rio 2007 - Duarte, Fabrício Luís (2012)
The objective of this dissertation consists in understand the production of the Pan American Games Rio 2007 in the context of "advanced" capitalism. The discussion is guided by a literature review, as well as documentary research, which includes news from newspapers, magazines, websites and official documents about this mega sports events. It is evident that the Pan American Games Rio 2007, created through extensive state financial resources, were marked by a wasteful production in which the decreasing utilization rate assumes the dominant position, especially in relation to sports equipment. In this field, the International Olympic Committee, the Brazilian Olympic Committee and Rio 2007 Organizing Committee are understood as hegemonic apparatus, as "organisms" of "civil society" responsible for political, moral, cultural and ideological leadership: those institutions work stimulating volunteering , spreading the sport transformed into a commodity, as well as promoting the sports culture of high performance. Finally, some questions are raised for future researches, especially a debate about the estrangement in the sport of high performance, whose suppression is irrevocable condition to effective humanization of the sport.